Ossicular Erosion in Patients Requiring Surgery for Cholesteatoma - Ghodrat Mohammadi; Masoud Naderpour; Mehrnoosh Mousaviagdas (Iranian Journal of Otorhinolaryngology, 2012)
Introduction: The aim of this study was to evaluate the condition of the ossicular chain in patients requiring surgery for cholesteatoma. Materials and Methods: In a retrospective analysis, the destruction of the individual and combined bony structures of the ear was described in 166 patients with cholesteatoma who went through surgery in our Otology Center between 2003 and 2009. Results: Total (55.4%) or partial (30.7%) erosion of the incus was the most common pathology. In some cases, the long process (25.9%) and the body of incus (4.8%) were also involved. Erosion of the stapes superstructure occurred more commonly than a total loss of the bone (40.9% vs. 25.9%). Erosion of the malleus was least common. Completely intact ossicles were present in 5.5% of cases. Total ossicular erosion with an intact footplate (18.7%) and incudostapedial erosion (18%) was the most common combination of ossicular erosion. All patients with incudostapedial erosion had advanced disease (85% with multiple site involvement). Conclusion: Widespread cholesteatoma results in greater ossicular erosion and poor hearing outcomes.